TEACHER COMMUNICATION COMPETENCE IN TEACHING THROUGH ONLINE PROCESSES AT SMK SATRIA JAKARTA ACADEMIC YEAR 2021/2022 - Indra Mulya Pratama (MediaKom : Jurnal Ilmiah Komunikasi, 2021)
This study aims to describe and analyze teacher communication competencies in teaching through the online process during the 2021/2022 academic year at SMK Satria Jakarta. Teaching and learning activities (KBM) through the online process are one of the new challenges for teachers, where teachers do not teach face-to-face and take advantage of the existing internet network. The research method used by the author is a case study. The type of case study method is an intrinsic case study, where the author wants a better understanding of the case to be studied. The results of this study describe communication competence in the online learning process. Communication between teachers and students in teaching through the online process has a positive impact on communication competencies that continue to develop, Therefore in this sub-chapter the communication competence of teachers at SMK Satria Jakarta is analyzed through five dimensions of communication competence, namely the dimensions of motivation, the dimensions of knowledge, the dimensions of skills. , the dimension of attitude, the emotional dimension in order to produce an in-depth analysis. It is known that the pedagogic competence of teachers at SMK Satria Jakarta is able to manage online learning for students. In addition, in personality competence, teachers at SMK Satria Jakarta have personality competencies that can be role models in communicating. In social competence, teachers at SMK Satria Jakarta have social skills which are one of the competencies in the teacher's personality that can distinguish the approach between teachers and students. In professional competence, the teachers at SMK Satria Jakarta have competence according to their respective fields, this is one of the keys to being able to maintain good communication between teachers and students. And finally, the communication competence of teachers at SMK Satria Jakarta in carrying out online learning continues to grow, and can be in line with the theory of gestalt learning and the theory Social Construction of Technology